Protecting Financial Institutions from Brute-Force Attacks - Herley, Cormac; Florencio, Dinei (Springer-Verlag, 2008)
We examine the problem of protecting online banking accounts from password brute-forcing attacks. Our method is to create a large number of honeypot userID-password pairs. Presentation of any of these honeypot credentials causes the attacker to be logged into a honeypot account with fictitious attributes. For the attacker to tell the difference between a honeypot and a real account he must attempt to transfer money out. We show that is simple to ensure that a brute-force attacker will encounter hundreds or even thousands of honeypot accounts for every real break-in. His activity in the honeypots provides the data by which the bank learns the attackers attempts to tell real from honeypot accounts, and his cash out strategy.
Proceedings of the 1999 Haskell Workshop